Synthesis and characterization of HDTMA-organoclays: Insights into their structural properties - Naranjo, Pablo Matias (2015)
This study aims to synthesize and characterize organoclays developed from an Argentinian montmorillonite (Bent) using hexadecyltrimethylammonium bromide (HDTMA-Br) as the intercalation agent. Subsequently, an adsorption mechanism is proposed. The obtained organoclays were more hydrophobic than the starting clay. Surfactant molecules were adsorbed initially through cation exchange in sites placed in the interlayer space of the clay. Adsorption in such sites continued until the interlayer space was saturated. Depending on the surfactant loading introduced during the intercalation process, different organizations of surfactant in the interlayer were obtained. Further adsorption of surfactant occurred in the mesopores generated by tactoids in the "house of cards" organization. This process kept surfactant molecules relatively free and out of the interlayer space.